Topical Gel of Mesenchymal Stem Cell-Conditioned Medium-induced Serum Injury Accelerates Wound Healing in Skin Excision Tissue - Berlian, Mukti Arja; Alif, Iffan; Subchan, Prasetyowati; Handoyo, Frigi Eko; Husain, Sofian Azalia; Husni Ahmad Sidiq; Arlinda, Dyken Dwi; Adityani, Resanti (Stem Cell and Cancer Research (SCCR), 2022)
Introduction: Umbilical cord-derived mesenchymal stem cells (UC-MSCs) accelerating wound closure by increasing VEGF and PDGF level leading to re-epithelialization, cell infiltration, and angiogenesis. It has been found that MSC-conditioned medium (MSC-CM) can enhance migration of fibroblasts in scratch assays. However, the effect of MSC-CM-induced serum injury (MSC-CM-S) formulated in gel to accelerate wound healing remains unclear. This study aims to evaluate the effect of several doses of topical gel of MSC-CM-S in accelerating wound healing. Methods: The MSCs were cultured medium-supplemented serum injury of wounded rat (8:1) to get MSC-CM-S. The topical gel of MSC-CM-S was made by base gel supplemented with MSC-CM-S. Eighteen Wistar rats were randomly assigned into control (C) and treatment groups (T1, T2). Groups were received serum-free medium gel (C), 25 µl MSC-CM-S in topical gel (T1), 50 µl MSC-CM-S in topical gel (T2), twice daily for 9 days. PDGF and VEGF level and fibroblast density were measured by ELISA and HE staining at day 3 and 6, respectively. Results: This study showed that there was significant increase of VEGF and PDGF level along with a significant increase of fibroblast density at day 3 and 6. The T2 showed optimum enhancement level of VEGF, PDGF and fibroblast density. Conclusion: Topical gel of MSC-CM-S was effective to accelerate wound closure by enhancing PDGF and VEGF level in full-thickness skin defect rats.